Pursuing individualism without feminism: Leisure life and gender politics of young female bar‐goers in urban China. (11th October 2022) - Huang, Yanhua; Liu, Zixi
Abstract: Drawing upon fieldwork data collected among young female bar‐goers in China, we examine the gender politics manifested by their leisure activities and argue that these young women are pursuing individualism without feminism. By analyzing the act of bar hopping, we reveal the internal tension of individuation, which urges women to engage in gender labor in order to obtain preferential treatment regarding consumption and a competitive advantage in esthetic femininity. This indicates that the central axis of Chinese women's individualization is a hybrid of neoliberal individuals and essentialist gender roles. It encourages women to see themselves voluntarily as subordinate subjects in market transactions and feminized objects under male scrutiny. The pursuit of individualism without feminism prevents women from overcoming the highly gendered settings of bar scenarios, or imagining the female as a whole group with communal solidarity. The Chinese female individual manifests herself as a hostage of the collusion between the commodification of social life and a conservative gender regime. The case of China brings the individualization thesis out of its original compressed‐modernity framework and indicates that East Asia's quest for modernity must address the compressed conditions of individualism and feminism simultaneously.